"No One Ever Even Asked Me that Before": Autobiographical Power, Social Defeat, and Recovery among African Americans with Lived Experiences of Psychosis. (13th September 2016) - Myers, Neely Anne Laurenzo; Ziv, Tali
Abstract : Our article draws on ethnographic research with African American males diagnosed with a psychotic disorder in a high‐poverty urban area of the northeastern United States. Our participants frequently described the ways public mental health services led them to experience a paralyzing erosion of autobiographical power, which we define as the ability to tell one's own story and be the editor of one's own life. We identified three important points when the loss of autobiographical power seemed to perpetuate social defeat or a sense of social powerlessness (Luhrmann 2007) for our participants during their interactions with public mental health care. We invite further inquiry into the loss of autobiographical power in settings of public mental health care, the sense of social defeat it seems to perpetuate, and the impact of these on mental health recovery, especially for people living in contexts of persistent social adversity.